Phylogeography of a polymorphic southern African endemic species, the southern boubou laniarius ferrugineus (gmelin, 1788) - Molepo, Dikobe Karen (My University, 2019)
It cannot be overemphasised that birds, which form a group of animals that are conspicuous in many habitats, occur worldwide, and are ecologically diverse and better known than any other vertebrate groups. Some species present no geographical variation while others exhibit complex geographic variation rendering them polytypic. The Southern Boubou Laniarius ferrugineus (Gmelin, 1788) is a polymorphic and highly vocal resident species endemic to Southern Africa. It overlaps with the Tropical Boubou Laniarius aethiopicus in the extreme north of South Africa. The taxonomic circumscription presents six subspecies of L. ferrugineus which vary in size and plumage colourations. Although L. ferrugineus is of least concern (LC), its wide distribution range calls for its precise taxonomic delineation and our knowledge of its genetic structure hence the need to investigate the status and level of morphological, genetic and vocal differentiation in this species complex. Morphological, genetic and song variation were analysed from museum study skins, DNA sequences spanning one coding mitochondrial gene and three noncoding nuclear introns generated from modern and ancient samples and songs from various sound libraries respectively. While morphometric analyses and Bayesian phylogenetic inference recovered two major lineages in L. ferrugineus: 1) L. f. ferrugineus / L. f. pondoensis / L. f. natalensis (southern clade) and 2) L. f. transvaalensis / L. f. tongensis / L. f. savensis (northern clade), L. f. transvaalensis overlapped between the two lineages in MDS and Box and whisker plots. The 95% parsimony ATP6 network similarly revealed two distinct lineages with the population demographic histories of the two clades showing expansion. The divergence between the two lineages occurred approximately 1.5 million years ago during the Pleistocene epoch. Laniarius ferrugineus pondoensis is the most distinctly dark morph. The moist habitat of L. f. pondoensis could be having an effect on plumage while there is no genetic basis for the difference in plumage colouration. Almost all L. ferrugineus subspecies render a tonal song duet made up of ‘bou’ and ‘whistle’ elements with the significant difference being observed in maximum peak frequency. Laniarius ferrugineus (Gmelin, 1788) should at best be split into two species, one representing members of the southern clade to be named Laniarius ferrugineus (Gmelin, 1788) and another species representing members of the northern clade iv named Laniarius transvaalensis Roberts, 1922 based on the Principle of Priority. The current study expanded our knowledge base as far as ornithology is concerned and shed light on the phylogeographic patterns of the Southern Boubou Laniarius ferrugineus (Gmelin, 1788). The findings significantly contributed to our understanding of the evolutionary processes governing the geographical variation in Laniarius ferrugineus complex and the findings could possibly be extrapolated to other species. It was critical that the taxonomic affinities of L. ferrugineus were investigated due to its extensive distribution range for better management and conservation. Future work should further unravel the less differentiation within the south and north lineages with additional songs being analysed to understand the song pattern across the range.
Thesis (M.Sc. (Zoology)) -- University of Limpopo, 2019
Keywords: Birds; Phylogeography; Birds -- Africa, Southern; Phylogeography; Endemic birds